Historical Integration of Modern Urban Fabrics Using Place Making as a Tool - Jenitta Paha (Multidisciplinary Journal of Akseprin Indonesia, 2024)
Historic sites represent the identity of the city. The rapid urbanization and city-making process have led to the decay and neglect of historical sites. To recover historical sites from the decline process, a place-making approach is used as a tool. Complex areas, with a historical urban fabric symbolizing the city's origins and often linked to important historical buildings, form the center of historical cities in India. These areas serve as a central point of identity for the entire city and are often endowed with notable heritage buildings. One such historical location in India is the coastal stretch of Manapad. The town is referred to as "Little Jerusalem." The unplanned developments have tarnished the city's image by destroying its historical urban fabric and identity. The study's methodology is based on a field survey that uses a visual survey approach to collect data through the use of techniques like photography, diagrams, or maps, as well as the analysis of various literature to understand the components of the urban fabric, historical evolution, growth, and development. The study attempts to analyze the urban fabric of historic sites, identify factors affecting it, and suggest strategies and measures for integrating the historic vestiges into the modern urban fabric. The proposed strategies are some of the tools and techniques that could be adopted by urban designers, planners, and local planning authorities in improving the urban fabric of historic sites.